1999
DOI: 10.1085/jgp.114.2.215
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Voltage-Dependent Gating and Open-State Stability in the S5 Segment of Shaker Potassium Channels

Abstract: The best-known Shaker allele of Drosophila with a novel gating phenotype, Sh 5, differs from the wild-type potassium channel by a point mutation in the fifth membrane-spanning segment (S5) (Gautam, M., and M.A. Tanouye. 1990. Neuron. 5:67–73; Lichtinghagen, R., M. Stocker, R. Wittka, G. Boheim, W. Stühmer, A. Ferrus, and O. Pongs. 1990. EMBO [Eur. Mol. Biol. Organ.] J. 9:4399–4407) and causes a decrease in the apparent voltage dependence of opening. A kinetic study of Sh 5 revealed that changes in the deactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 95 publications
1
38
0
1
Order By: Relevance
“…9B, bottom) and Leu 371 in S4. This structural arrangement is consistent with the strong impact on voltage sensitivity of mutating these amino acids, and with the assigned role of S5 in regulating the final steps in activation that leads to channel opening (16,48). Thus, our functional findings on a hybrid Kv/KcsA channel also question the structural arrangement that emerged from the KvAP crystals, and favor a more conventional type of conformation for Kv channels.…”
Section: Mutations At the N Terminus Of S5 Segment In The Shakerkcsa supporting
confidence: 84%
“…9B, bottom) and Leu 371 in S4. This structural arrangement is consistent with the strong impact on voltage sensitivity of mutating these amino acids, and with the assigned role of S5 in regulating the final steps in activation that leads to channel opening (16,48). Thus, our functional findings on a hybrid Kv/KcsA channel also question the structural arrangement that emerged from the KvAP crystals, and favor a more conventional type of conformation for Kv channels.…”
Section: Mutations At the N Terminus Of S5 Segment In The Shakerkcsa supporting
confidence: 84%
“…dues Arg-394, Glu-395, Leu-398, and Tyr-485, which we will abbreviate as RELY interaction, stabilizing the activated state of the channel. Nevertheless, concerns that the slow off-gating component may not develop at physiological conditions need to be addressed as it had been suggested that the non-conducting phenotype of W434F Shaker channels is due to C-type inactivation and that the slow off-gating component arises from this feature (40,41), although results of other authors are more consistent with an open state stabilization than with C-type inactivation (11,13). In addition, it had been proposed that different permeant ions variably alter the kinetics of the off-gating currents (11,12,42).…”
Section: Table 2 Summary Of Ionic Current and Fluorescence Results Inmentioning
confidence: 99%
“…The slow off-gating component has also been proposed to be dependent on the permeant ion (6,11,12) and was thought to be linked to C-type inactivation (11). Other authors, however, view it rather as a stabilization of the open state (13). Although theoretical descriptions of off-gating currents have been proposed (14 -16), the correlating structural determinants underlying these patterns remain unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The S4 segment stands out by virtue of having 6 -9 positively charged amino acids (either lysine or arginine) out of ϳ20. Membrane depolarization is believed to open the channel through an S4-mediated conformational change (256,302,318,364,425,434,514). The recent X-ray structure of the voltage-gated K ϩ channel has shown that S1-S4 helices are attached to the pore region and the latter half of S3 and S4 form the voltage sensor (245,246).…”
mentioning
confidence: 99%